Synthesis and swelling behaviour of bentonite based superabsorbent polymer composite - Muhammad Danial, Mazelan (2012)
Bentonite based superabsorbent polymer composite(SPCwas synthesized by solution polymerization of acrylic acid and acrylamide comonomer with bentonite using ammonium persulfate(APS)as an initiator and N, N-methylenebisacrylamide(MBA)as a crosslinker.Amount of bentonite,initiator and crosslinker were varied to get the optimum value to produce maximum water absorbency.The water absorbency determination was done by using tea-bag method The SPC were characterized by using Fourier Transform Infrared Spectroscopy(FTIR)and Thermogravimetric Analysis (TGA).The water absorbency under optimal synthesis of the SPC with Bentonite content of 10%, APS content of 0.9% and MBA content of 0.0%,it reaches more than 537 g H2O/g in distilled water respectively.